2021
DOI: 10.1111/1475-6773.13732
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving during the Time of COVID‐19: A Multi‐State Qualitative Study of Family Caregiver Experiences and Decision‐Making

Abstract: Research Objective COVID‐19 poses unique challenges to family caregivers. This study explores how family caregivers for older adults with cognitive impairments experience and make decisions about caregiving during a global pandemic. Study Design Using purposive sampling, family caregivers participated in open‐ended qualitive interviews (2019–2020), until thematic saturation was reached. Questions broadly examined caregivers' experiences and decisions, focusing on decisions made around type of care setting. Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…Our findings contribute to the sparse literature on caregivers of adults with epilepsy and literature on the impacts of COVID-19 on informal caregivers. Consistent with other caregiving research, we found COVID-19 increased caregiver distress and burden [13] , [18] , [19] , [20] and specifically for caregivers of adults with epilepsy. Because epilepsy can affect both adults with epilepsy and their informal caregivers [8] , it is crucial to understand how caring for individuals with epilepsy can influence caregivers, and how these influences differ compared to caregivers of children or adolescents with epilepsy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings contribute to the sparse literature on caregivers of adults with epilepsy and literature on the impacts of COVID-19 on informal caregivers. Consistent with other caregiving research, we found COVID-19 increased caregiver distress and burden [13] , [18] , [19] , [20] and specifically for caregivers of adults with epilepsy. Because epilepsy can affect both adults with epilepsy and their informal caregivers [8] , it is crucial to understand how caring for individuals with epilepsy can influence caregivers, and how these influences differ compared to caregivers of children or adolescents with epilepsy.…”
Section: Discussionsupporting
confidence: 91%
“…While the relationship between caregiving and health is generally associated with stress [10] , it is crucial to understand other factors that contribute to the overall burden experienced by epilepsy caregivers and how their well-being is affected over the course of their caregiving role [10] , [11] . The ongoing COVID-19 pandemic [12] has posed, and continues to pose, unprecedented challenges to caregivers of all types of conditions [13] , including epilepsy. A deeper understanding of the current factors influencing the health, well-being, and QOL of epilepsy caregivers is necessary to provide valuable insights into these circumstances, and ultimately to address high levels of caregiver burden in both pandemic and non-pandemic settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, concerns from family members arose with the level and focus of communications in respect of continuing restrictions and the slow reintroduction of visiting. In agreement with Sadler et al’s [ 16 ] findings, strengthening communication supports when residential care facilities are locked down may reduce confusion and feelings of isolation for residents. Furthermore, Staker and Sun Choi [ 17 ] concur that families feel peace of mind when there are multiple communication channels for them to contact the resident.…”
Section: Discussionsupporting
confidence: 90%
“…Although the authors did not specifically analyze Levesque’s framework, they nevertheless utilized terms similar or identical to those in the framework. Half of the studies reported the availability (or lack) of healthcare resources due to financial insecurities, a lack of healthcare insurance, education/knowledge gaps, transportation, Internet/phone or telemedicine, cognitive screening, ambulatory care, and so on ([ 26 , 36 , 37 , 38 , 39 ]) (See Table 4 ). These were grouped as materials, financial insecurities, and knowledge gaps.…”
Section: Resultsmentioning
confidence: 99%